The Definitive Guide to HTML5 - Freeman, Adam. (Apress : Imprint: Apress, 2011)
The Definitive Guide to HTML5 provides the breadth of information you'll need to start creating the next generation of HTML5 websites. It covers all the base knowledge required for standards-compliant, semantic, modern website creation. It also covers the full HTML5 ecosystem and the associated APIs that complement the core HTML5 language. The Definitive Guide to HTML5 begins by tackling the basics of HTML5, ensuring that you know best practices and key uses of all of the important elements, including those new to HTML5. This section also covers extended usage of CSS3, JavaScript, and DOM manipulation, making you proficient in all core aspects of modern website creation. The final part of the book covers the associated W3C APIs that surround the HTML5 specification. You will achieve a thorough working knowledge of the Geolocation API, web storage, creating offline applications, and the new drag and drop functionality. The Definitive Guide to HTML5 also dives into the key media enhancements of HTML5 and its surrounding technologies: Canvas, video and audio.